2020
DOI: 10.31925/farmacia.2020.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Factors’ Influence on Adherence to Antihypertensive Medication

Abstract: Non-adherence to antihypertensive medication is commonly associated with suboptimal clinic outcomes but is nonetheless a common behaviour. This observational study investigated medication adherence of hypertensive Romanian patients using the Morisky-Green-Levine questionnaire. 22.2% of patients had low adherence, 51.3% of patients had moderate adherence and 26.5% had high adherence. Investigating the influence of age, sex, education, medication regimen complexity, comorbidities and information about medicines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…We also quantified patients' adherence to medication, based on the superposition of drugs prescribed and those dispensed. Non-adherence to antihypertensive drugs reaches significant levels in Romanian patients, as previous studies revealed [19,24].…”
Section: Introductionmentioning
confidence: 78%
“…We also quantified patients' adherence to medication, based on the superposition of drugs prescribed and those dispensed. Non-adherence to antihypertensive drugs reaches significant levels in Romanian patients, as previous studies revealed [19,24].…”
Section: Introductionmentioning
confidence: 78%